Long-term change in rainfall distribution in Northeast Thailand: will cropping systems be able to adapt? - Lacombe, Guillaume; Polthanee, Anan; Trébuil, Guy (EDP Sciences, 2017)
Climate vagaries and the lack of irrigation, frequently combined with coarse-textured sandy and unevenly distributed saline soils, explain low crop yields and the endemic relative poverty of the rural population in Northeast Thailand (NET). Local and regional trends in agriculturally-relevant rainfall variables were investigated using the Mann-Kendall test, modified to account for serial correlation, and applied to 17 stations across NET, and the regional average Kendall's statistic. Limited changes in rainfall frequency, intensity and seasonality are observed at individual stations over the study period (1953–2004). But we found a significant regional trend toward a wetter dry season. Based on an intimate knowledge of the local farming systems, we discuss the cropping systems adaptation to these rainfall changes. If the wetting of the dry season extends in the future, as expected according to most climate projections, households would not find it difficult to adapt, except for the problems caused by temperature rise, mainly due to their renowned adaptive capacity and high mobility that historically produced diverse and resilient rural livelihood systems.